Isolated penile injury in boys: Accident, negligence, or abuse? - Nitin Pant; Sudhir Singh; Anand Pandey; Ashish Wakhlu (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study was to highlight the etiology, spectrum of presentation, and management of isolated penile trauma in boys. Methods: A retrospective review of boys treated for isolated penile trauma between January 2015 and June 2019 at a tertiary-level hospital. Results: Nine children were admitted over 4½ years. Etiology: The mechanism of penile injury (PI) was penile hair tourniquet (n = 5), postcircumcision (n = 2), dog bite (n = 1), and scald injury (n = 1). Extent of injury includes complete urethral transection at corona (n = 4); loss of urethral plate in a case of hypospadias (n = 1); complete loss of glans (n = 1); penile transection at corona (n = 1); total penile amputation (n = 1); and deep partial-thickness burns of penile shaft and adjacent suprapubic skin (n = 1). Management: One patient absconded. The remaining patients were managed as follows: calibration of urethral meatus (n = 1); penile burn was managed with dressing and antibiotics; coring of glans with urethral end-end anastomoses (n = 4); Bettocchi's quadrangular lower abdominal flap phalloplasty (n = 1); and Bracka's staged urethroplasty (n = 1). Complications include wound infection following trauma (n = 4), postsurgical infection (n = 3), urethrocutaneous fistula (n = 2), and reapplication of penile hair tourniquet (n = 1). Conclusion: Isolated PI in boys is not uncommon. Most are preventable if the parents are apprized and watchful. The clinician should also be vigilant regarding child maltreatment. A staged approach tailored to the type of injury provides a satisfactory outcome.